2011
DOI: 10.1371/journal.ppat.1001330
|View full text |Cite
|
Sign up to set email alerts
|

SLO-1-Channels of Parasitic Nematodes Reconstitute Locomotor Behaviour and Emodepside Sensitivity in Caenorhabditis elegans slo-1 Loss of Function Mutants

Abstract: The calcium-gated potassium channel SLO-1 in Caenorhabditis elegans was recently identified as key component for action of emodepside, a new anthelmintic drug with broad spectrum activity. In this study we identified orthologues of slo-1 in Ancylostoma caninum, Cooperia oncophora, and Haemonchus contortus, all important parasitic nematodes in veterinary medicine. Furthermore, functional analyses of these slo-1 orthologues were performed using heterologous expression in C. elegans. We expressed A. caninum and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 61 publications
1
53
0
Order By: Relevance
“…slo-1 gain-of-function mutations phenocopy the effects of emodepside and slo-1 null mutants are rescued by transformation with wild type slo-1 [77]. Orthologues of slo-1 from parasitic nematodes also restore emodepside sensitivity to the C. elegans loss-of-function mutants [78]. In contrast, a human orthologue of slo-1 does not confer emodepside sensitivity to these mutants, though it does rescue some of the behavioral deficiencies associated with the absence of the channel [79].…”
Section: Nematode Slo-1 Ca2+-activated Potassium Channels As Targets mentioning
confidence: 99%
See 1 more Smart Citation
“…slo-1 gain-of-function mutations phenocopy the effects of emodepside and slo-1 null mutants are rescued by transformation with wild type slo-1 [77]. Orthologues of slo-1 from parasitic nematodes also restore emodepside sensitivity to the C. elegans loss-of-function mutants [78]. In contrast, a human orthologue of slo-1 does not confer emodepside sensitivity to these mutants, though it does rescue some of the behavioral deficiencies associated with the absence of the channel [79].…”
Section: Nematode Slo-1 Ca2+-activated Potassium Channels As Targets mentioning
confidence: 99%
“…The current view appears to be that emodepside can act either directly or indirectly on SLO-1 channels. In the pharynx, emodepside apparently acts upstream of the SLO-1 channel, likely via the latrophilin receptor, to modulate SLO-1 activity, perhaps via phosphorylation, while the latrophilin receptor is not involved in emodepside activity on body wall musculature [78]. …”
Section: Nematode Slo-1 Ca2+-activated Potassium Channels As Targets mentioning
confidence: 99%
“…Given that J2 stage plant parasitic nematodes have to locate their host plant using sensory mechanisms, it will likely be helpful to use this information as a platform to inform functional studies on these pests. There is a strong precedent for this 'model hopping' approach in veterinary medicine where it has made a major contribution to understanding the mode of action of novel anthelmintics and highlighting new anthelmintic targets (Cully et al, 1994;Kaminsky et al 2008;Welz et al 2011). Thus, there is the promise that similar approaches may yield insight into plant parasitic nematodes and their control.…”
Section: The Futurementioning
confidence: 99%
“…To date, only one anthelmintic, emodepside, has been shown to require a voltage-gated ion channel for its activity (Guest et al, 2007;Welz et al, 2011). Emodepside inhibits locomotion, feeding, egg-laying and slows development of C. elegans and parasitic worms Willson et al, 2003;Bull et al, 2007;Welz et al, 2011), and these multiple effects may be due to activation of more than one target.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…Emodepside inhibits locomotion, feeding, egg-laying and slows development of C. elegans and parasitic worms Willson et al, 2003;Bull et al, 2007;Welz et al, 2011), and these multiple effects may be due to activation of more than one target. Following a screen to identify C. elegans mutants resistant to emodepside, it was found that worms with loss-of-function mutations in slo-1, a gene that encodes a voltage-and calcium-activated potassium, or BK, channel (Atkinson et al, 1991), are resistant to emodepside inhibition of locomotion and pharyngeal pumping whereas gain-of-function mutants in the same gene phenocopy the action of the drug (Guest et al, 2007).…”
Section: Potassium Channelsmentioning
confidence: 99%